Smart Wi-Fi Traffic Assister (International Journal of Engineering and Computer Science, 2016)
Advancements of technology in mobile communications along with wide penetration in usage of Smart phones and its applications as well as increase in traffic densities at junctions in every major city leads to the development of Smart Wi-Fi Traffic Assister with signal overriding using RFID technology. The main purpose of such system is to alleviate the traffic congestion at the junctions by sending traffic density information from junction to Smartphone using Wi-Fi technology. The proposed system placed at traffic junction uses four sets of red, yellow and green LEDs, four IR sensors, RFID reader, Wi-Fi module all these connected to an ARM7 LPC2148 microcontroller. The IR sensor contains IR transmitter and IR receiver each one is placed on either sides of road like this we place all the IR sensors in a four road junction. The on and off condition of this IR sensor gives the density information at a particular road. Based on current traffic density at the four road junction, the microcontroller takes decision and updates the traffic light delays. The RFID technology is used to override the traffic signal if there is any emergency vehicle like ambulance, fire engine or VIP vehicle etc with an RFID tag at any road in a four road junction then the RFID reader reads the RFID tag and sends this signal to microcontroller then the green LED glows for that particular road. All the signals which cause change in normal operation of traffic signalling are continuously sent to users by Wi-Fi module and the user will get the traffic updates whenever required to his/her smart phone through a telnet application.